Breath therapy for patients with chronic nonspecific low back pain: A protocol of systematic review and meta-analysis. Issue 31 (31st July 2020) - He, Xu; He, Chunjiang; Luo, Xiaobing; Lu, Huaimin; Wu, Liang; Yu, Duoduo; Gao, Piming; Zhou, Wenqi; Shen, Hai; Yu, Yaming
Abstract: Background: Chronic nonspecific low back pain (CNLBP) has become a major global public health problem. Its high incidence rate and high disability rate are so damaging both to individuals and communities. At present, many countries' clinical guidelines recommend exercise therapy. Breath therapy is one of the exercise therapies, playing an important role in exercise therapy. Some studies have shown that breath therapy has a considerable therapeutic effect on low back pain, but there is no specific conclusion. The aim of our study is to answer the question: if breath therapy is effective and safe for CNLBP? Methods: The following databases will be searched: English databases (including Web of Science, the Cochrane Library (Central), EMBASE, MEDLINE, Allied and Alternative Medicine) and Chinese databases (including Chinese National Knowledge Infrastructure, Wanfang data and Chinese Scientific Journals Database [VIP]). The literature search will be constructed around search terms for breath therapy, search terms for chronic nonspecific low back pain and search terms for randomized controlled trials. The primary outcomes were related to duration, intensity, attack frequency of pain, and the secondary outcomes were related to physical function, quality of life, and adverse events related to interventions. Endnote software 9.1 will be applied in selecting study, Review Manager software 5.3 will be applied in analyzing and synthesizing. Results: The results will provide evidence to judge whether breath therapy is effective and safe for CNLBP. Conclusion: Our research will provide reliable evidence of breath therapy for CNLBP. Registration: International Prospective Register of Systematic Reviews (PROSPERO) CRD42020156340.